Beneficial effects of increasing dietary levels of raw lentil seeds on meat fatty acid and plasma metabolic profile in broiler chickens - CIURESCU, GEORGETA; VASILACHI, ANDREEA; ROPOTÃ, MARIANA; PALADE, MIHAI; DRAGOMIR, CÃTALIN (The Indian Journal of Animal Sciences, 2017)
The aim of the present study was to investigate the effect of diets containing raw lentil seeds (Lens culinaris cv. Eston and cv. Anicia) on meat fatty acids profile and blood plasma parameters of broiler chickens. Day old, broiler chicks (1,000; Cobb 500) were randomly allocated to the following 5 treatments, viz. a diet based on corn and SBM as control; 200g/kg of raw lentil seeds cv. Eston (LE); 400 g/kg of LE; 200g/kg of raw lentil seeds cv. Anicia (LA);400 g/kg of LA. Data were analysed as a 2 × 2 factorial arrangement. The broilers meat fatty acid profile was affected by dietary inclusion of lentil. Accordingly, breast muscle of broilers fed raw lentil seeds had significant higher levels of alfa-linolenic, eicosapentaenoic (EPA), docosapentaenoic and docosahexaenoic (DHA) acids. A significant interaction was observed between level and cultivar for majority of n-3 PUFA profile, except for octadecatetraenoic acid, EPA and DHA. The blood plasma parameters were not influenced by treatments, except for glucose and triglycerides concentration which were lower in the groups fed with lentils. No significant interaction between lentil levels and cultivars was noticed for plasma parameters. Based on the results, we concluded that raw lentil seeds represent an interesting alternative protein source which can improve the quality of broiler meat that can be recommended in healthy, balanced diets to prevent human diseases.